2011
DOI: 10.1093/rheumatology/ker277
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of osteonecrosis associated with corticosteroid therapy among different underlying diseases: prospective MRI study

Abstract: These findings suggest that the incidence of CS-associated osteonecrosis varies among different underlying diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
3
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 15 publications
5
94
3
8
Order By: Relevance
“…In the 1,502 patients whose detailed information was available, the potential causative factors of ONFH were largely attributable to systemic steroid administration (51 %), with SLE reported most frequently (31 %). Shigemura et al [20] investigated the relationship between underlying disease and risk factors for steroid-associated ONFH in a prospective MRI study. They reported that the incidence of ONFH was significantly higher in the SLE group than in the non-SLE group (37 % vs 21 %, P00.001).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1,502 patients whose detailed information was available, the potential causative factors of ONFH were largely attributable to systemic steroid administration (51 %), with SLE reported most frequently (31 %). Shigemura et al [20] investigated the relationship between underlying disease and risk factors for steroid-associated ONFH in a prospective MRI study. They reported that the incidence of ONFH was significantly higher in the SLE group than in the non-SLE group (37 % vs 21 %, P00.001).…”
Section: Discussionmentioning
confidence: 99%
“…7,8,[10][11][12] Glucocorticoid-induced osteonecrosis also complicates treatment of nonmalignant conditions such as solid organ transplant and arthritis. [13][14][15] Osteonecrosis can result in debilitation and adversely affect quality of life, often requiring surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main factors of predisposition to AVN is the presence of anti-phospholipid antibodies (APA) and/or anti-phospholipid syndrome. In a one-year prospective magnetic resonance imaging (MRI) study of 687 joints in patients with SLE, the risk factors for the increase in the incidence of AVN in comparison to patients with other autoimmune diseases such as myositis, medium-and large-vessel vasculitides, pemphigoid, RA, scleroderma and Behcet's disease were adult and adolescent patients (OR = 13.2), high glucocorticoid dose of more than 40 mg/d of prednisolone equivalent (OR = 4.2), patients with SLE (OR = 2.6) and the male sex (OR = 1.6) [21] . Treatment of AVN depends on the stage of the disease, the severity of the involvement of AVN, pain severity and the presence of co-morbidities which may pose patients to higher risks for major operation and anesthesia [23] .…”
Section: Fragility Fracturementioning
confidence: 99%
“…AVN AVN or osteonecrosis is not an uncommon phenomenon in SLE patients. Amongst all rheumatic diseases, the prevalence of AVN is the highest in patients with SLE, as compared with patients with other rheumatological conditions such as autoimmune myositis, vasculitides, rheumatoid arthritis (RA) and systemic sclerosis [21] . In one of the oldest studies, 4.6% of patients with SLE were found to develop AVN [22] .…”
Section: Fragility Fracturementioning
confidence: 99%